Preparation method of magnesium sulfate / diatomite composite thermochemical heat storage material
Through the preparation method of magnesium sulfate/diatomaceous earth composite thermal storage material, the liquid solution, poor thermal conductivity and stability of inorganic hydrated salt thermal storage materials are solved, and efficient heat storage and heat release are achieved, which is suitable for the recycling and utilization of low-grade energy and cross-season building heating.
Patent Information
- Application Number
- CN202411888994.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
The existing inorganic hydrated salt thermal chemical heat storage materials have problems such as liquid solution, poor thermal conductivity, deterioration of mass transfer during adsorption process and poor stability, making it difficult to effectively reduce the degree of liquid solution of the material and enhance the thermal conductivity and stability during recycling.
The preparation method of magnesium sulfate/diatomaceous earth composite thermal chemical heat storage material is adopted. By removing the moisture in diatomaceous earth, mixing deionized water with anhydrous magnesium sulfate powder, a uniformly mixed magnesium sulfate solution is prepared, and slowly dripped into the dried diatomaceous earth to ensure complete adsorption and drying, and a composite material with a high energy storage density is prepared.
It realizes efficient heat storage and heat release of materials, reduces heat loss, improves energy storage density and stability, and is suitable for the recycling of low-grade energy and cross-season building heating.
Smart Images

Figure CN119709138A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of inorganic hydrated salt medium- and low-temperature heat storage materials, and particularly relates to a preparation method of a magnesium sulfate / diatomaceous earth composite thermochemical material. Background Art
[0002] Long-term cross-seasonal heat storage technology is particularly important, including sensible heat storage, latent heat storage and thermochemical heat storage. Their heat storage technology principles are the same, that is, storing heat when the heat demand is small and releasing heat when the heat demand is high.
[0003] Among the three methods, sensible heat storage is the simplest and the lowest cost. Sensible heat storage materials are mainly divided into two categories: liquid medium and solid medium. The principle is to store heat at high temperature and release heat at low temperature. However, due to the existence of temperature difference, a large amount of heat loss will be caused, and the heat storage efficiency is low. It is not an effective long-term heat storage technology. Phase change heat storage uses the phase change enthalpy of phase change materials, that is, changing the phase (gaseous, solid, liquid) of the material without changing the temperature of the material to release and store heat. Compared with sensible heat storage, the phase change heat storage density is 5-14 times higher, which can effectively reduce the volume of the heat storage device, but the heat storage capacity will decrease with the increase of the number of cycles. Compared with sensible heat and phase change heat storage, thermochemical adsorption heat storage has the advantages of high heat storage density, small heat dissipation loss, and integration of heat storage and cold storage. Among them, inorganic hydrated salt thermochemical adsorption energy storage technology has the advantages of high heat storage capacity, energy saving and environmental protection, and simple system. It is suitable for the application of low-grade solar energy and industrial waste heat in building heating and air-conditioning. However, the liquefaction of inorganic salts will cause material loss and corrosion of containers. Inorganic salt materials have the disadvantages of poor thermal conductivity, deteriorated mass transfer in the adsorption process, and poor stability. Therefore, how to effectively reduce the degree of liquefaction of materials and enhance thermal conductivity and stability during cyclic use is one of the main research issues at present. At present, many researchers have conducted extensive research on hydrated salts. For example, in the literature Performance analysis of athermochemical based heat storage as an addition to cogeneration systems, researchers believe that MgSO4 and CuSO4 have ideal theoretical heat storage density. However, when pure salt is used as a thermochemical heat storage material, it often has certain disadvantages. For example, pure salt often cannot control the amount of water absorbed, resulting in liquid decomposition, which leads to the loss of heat storage materials and corrosion of containers; during the water absorption process, some salts may also form a dense salt shell on the surface during the adsorption process, resulting in a decrease in the overall heat release performance. Therefore, porous materials should be selected as the matrix, such as zeolite, diatomaceous earth, expanded vermiculite, expanded graphite, silica gel and other materials to adsorb hydrated salts to make porous composite thermochemical heat storage materials to reduce the impact of adverse factors.
[0004] This invention has important application value for utilizing China's abundant magnesium resources. my country's Qinghai Salt Lake, Qaidam Basin and Xinjiang Lop Nur area are rich in magnesium resources. The total amount of various magnesium salts that have been proven has reached 6.05 billion tons, accounting for 96.78% of the country's reserves, of which 1.6 billion tons are magnesium sulfate. The effective utilization of magnesium salts has become a key way to promote the development of salt lake resources in my country. Therefore, the research and development of thermochemical heat storage materials based on magnesium salts, and the use of their heat storage process to solve energy-saving problems in the fields of solar thermal energy utilization, industrial waste heat recovery, seasonal energy storage, and building heating, has important economic value for expanding the high-value utilization of magnesium resources. Summary of the invention
[0005] The method for preparing the magnesium sulfate / diatomite composite thermochemical heat storage material according to claim 1 is characterized in that the specific steps are as follows:
[0006] (1) Weigh a certain mass of porous material diatomaceous earth and place it in a drying oven for a period of time to remove the moisture that may be adsorbed therein. After drying, seal and store it.
[0007] (2) Deionized water and anhydrous magnesium sulfate powder are mixed, stirred for a while, and then placed in an ultrasonic cleaning machine for full stirring to obtain uniformly mixed magnesium sulfate solutions with different mass fractions.
[0008] (3) slowly dripping the magnesium sulfate solution obtained in step (2) into the porous material diatomaceous earth obtained by drying in step (1), keeping the surface of the diatomaceous earth dry during the dripping process until the adsorption is complete, leaving it to stand at room temperature for a period of time, and then placing it in a drying oven for drying. After drying, it is stored in a dry environment to obtain a magnesium sulfate / diatomaceous earth composite thermochemical heat storage material.
[0009] The porous material diatomaceous earth described in steps (1) and (3) is 200 mesh diatomaceous earth.
[0010] In step (2), the mixing mass ratio of deionized water to anhydrous magnesium sulfate powder is (10-2):1.
[0011] The stirring time of the solution in step (2) is 3 h.
[0012] The mass of the solution impregnated in step (3) is about twice the mass of the diatomaceous earth, and the solution is placed indoors for 10 to 12 hours, the drying temperature is 150° C., and the drying time is 12 hours.
[0013] The beneficial effects of the present invention are:
[0014] 1. The present invention pre-treats the porous material diatomite before the experiment, thereby removing the influence of the possible residual moisture in the diatomite on the subsequent experiments.
[0015] 2. The preparation method of the present invention is simple, easy to operate, and can be mass-produced. The overall experimental process does not produce chemical reactions, which is operator-friendly.
[0016] 3. The raw materials of the preparation method of the present invention have stable chemical properties, wide sources and low prices, and are suitable for large-scale long-term cross-seasonal energy storage scenarios.
[0017] 4. The composite thermochemical energy storage material manufactured by the present invention can be used at a temperature of less than 300°C and can store most of the energy under the working condition of 150°C, which is suitable for the recycling of low-grade energy, such as industrial waste heat recovery and solar energy collection. In addition, the material of the present invention has a large energy storage density, can store energy for a long time across seasons and maintain a small heat loss, is economical and environmentally friendly, and does not produce harmful substances. It is an excellent thermochemical heat storage material suitable for cross-season building heating. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the SEM result of the dried porous material diatomite after magnification 2000 times;
[0019] Figure 2 This is the SEM result of magnesium sulfate / diatomite composite thermochemical heat storage material with a loading rate of 18% after being magnified 2000 times;
[0020] Figure 3 The SEM result of magnesium sulfate / diatomite composite thermochemical heat storage material with a loading rate of 55% after magnification 2000 times;
[0021] Figure 4 This is the X-ray diffraction pattern (XRD) of magnesium sulfate / diatomite composite thermochemical heat storage material with a loading rate of 48%. DETAILED DESCRIPTION
[0022] The present invention provides a method for preparing a magnesium sulfate / diatomite composite thermochemical energy storage material, which will be further described below in conjunction with the accompanying drawings.
[0023] An electronic analytical balance (BT125D) is used to weigh the porous material diatomaceous earth before and after drying. When the masses of the two do not change after the most recent weighing, the sample is dried.
[0024] The microstructure of the dried diatomite powder was observed using a scanning electron microscope (ZEISS). Figure 1 As shown, the pores of the diatomaceous earth particles after drying are clear. Figure 2 and Figure 3 SEM images of magnesium sulfate / diatomite composite thermochemical heat storage materials with loading rates of 18% and 55% after magnification 2000 times. Figure 1 , Figure 2 , Figure 3It can be seen that as the loading rate increases, the coverage rate of salt on the diatomaceous earth surface becomes higher.
[0025] The crystal structure of the prepared magnesium sulfate / diatomite composite thermochemical heat storage material was studied by XRD diffractometer. Figure 4 As shown, the diffraction peak of magnesium sulfate is 21.79°, and the diffraction peak of diatomaceous earth is 21.93°, indicating that magnesium sulfate and diatomaceous earth have good compatibility, and the peak of the prepared composite material has both the peaks of magnesium sulfate and diatomaceous earth, which also verifies that no other substances are produced in the preparation process and the composite effect is good.
[0026] The magnesium sulfate / diatomite composite thermochemical energy storage material prepared by the present invention can be used at a temperature of less than 300°C, and the optimal use temperature is 150°C. Within this range, the energy storage density of the composite material is significantly higher than that of diatomite, but lower than that of pure salt. This is because diatomite itself does not absorb water. As the diatomite content in the composite material increases, the heat storage density will also decrease. Under the experimental conditions of 20°C and 80% humidity, the maximum adsorption capacity of the porous material diatomite is 0g (water) / g (material), and the maximum adsorption capacity of pure salt is 0.45g (water) / g (material), which is consistent with the literature 0.47g (water) / g (material). The maximum water absorption capacity of the composite material is 0.34 (water) / g (material), and the adsorption data is consistent with the enthalpy data.
[0027] Example 1
[0028] Weigh 10g of porous material diatomaceous earth powder, place it in a drying oven, dry it at 150°C for 12h, take it out and cool it to room temperature, then store it in a dry place, weigh 4g of anhydrous magnesium sulfate powder and 40g of deionized water to prepare a magnesium sulfate salt solution, weigh 10g of dried diatomaceous earth, slowly drop the prepared salt solution into the diatomaceous earth powder, gently stir when adding the solution to ensure uniform adsorption without destroying the porous structure of the diatomaceous earth, and ensure that the diatomaceous earth is apparently dry until the adsorption is complete, let it stand at room temperature for 4h to allow the salt solution to evenly penetrate into the pores of the diatomaceous earth, then place the wet composite material in a drying oven, evacuate it to 0.08MP to accelerate the separation of moisture, keep it at a constant temperature of 150°C for 10h to fully remove moisture, and obtain a magnesium sulfate / diatomaceous earth composite thermochemical heat storage material with a loading rate of 18%.
[0029] Weigh 5 g of the prepared composite thermochemical heat storage material and place it in a glass container. Set the constant temperature and humidity chamber temperature to 25°C and the relative humidity to 80% RH. After the working conditions of the constant temperature and humidity chamber are stable, put the glass container containing the composite material in and adsorb the composite material. During this period, record the weight every 30 minutes until the weight no longer increases. Finally, the adsorption amount of the magnesium sulfate / diatomaceous earth composite thermochemical heat storage material is 0.116 g (water) / g (material).
[0030] Example 2
[0031] Weigh 10g of porous material diatomaceous earth powder, place it in a drying oven, dry it at 150°C for 12h, take it out and cool it to room temperature, then store it in a dry place, weigh 8g of anhydrous magnesium sulfate powder and 40g of deionized water to prepare a magnesium sulfate salt solution, weigh 10g of dried diatomaceous earth, slowly drip the prepared salt solution into the diatomaceous earth powder, gently stir when adding the solution to ensure uniform adsorption without destroying the porous structure of the diatomaceous earth, and ensure that the diatomaceous earth is apparently dry until the adsorption is complete, let it stand at room temperature for 4h to allow the salt solution to evenly penetrate into the pores of the diatomaceous earth, then place the wet composite material in a drying oven, evacuate it to 0.08MP to accelerate the separation of moisture, keep it at a constant temperature of 150°C for 10h to fully remove moisture, and obtain a magnesium sulfate / diatomaceous earth composite thermochemical heat storage material with a loading rate of 32%.
[0032] Weigh 5 g of the prepared composite thermochemical heat storage material and place it in a glass container. Set the constant temperature and humidity chamber temperature to 25°C and the relative humidity to 80% RH. After the working conditions of the constant temperature and humidity chamber are stable, put the glass container containing the composite material in and adsorb the composite material. During this period, record the weight every 30 minutes until the weight no longer increases. Finally, the adsorption amount of the magnesium sulfate / diatomaceous earth composite thermochemical heat storage material is 0.20 g (water) / g (material).
[0033] Example 3
[0034] Weigh 10g of porous material diatomaceous earth powder, place it in a drying oven, dry it at 150°C for 12h, take it out and cool it to room temperature, then store it in a dry place, weigh 12g of anhydrous magnesium sulfate powder and 40g of deionized water to prepare a magnesium sulfate salt solution, weigh 10g of dried diatomaceous earth, slowly drop the prepared salt solution into the diatomaceous earth powder, gently stir when adding the solution to ensure uniform adsorption without destroying the porous structure of the diatomaceous earth, and ensure that the diatomaceous earth is apparently dry until the adsorption is complete, let it stand at room temperature for 4h to allow the salt solution to evenly penetrate into the pores of the diatomaceous earth, then place the wet composite material in a drying oven, evacuate it to 0.08MP to accelerate the separation of moisture, keep it at a constant temperature of 150°C for 10h to fully remove moisture, and obtain a magnesium sulfate / diatomaceous earth composite thermochemical heat storage material with a load rate of 48%.
[0035] Weigh 5 g of the prepared composite thermochemical heat storage material and place it in a glass container. Set the constant temperature and humidity chamber temperature to 25°C and the relative humidity to 80% RH. After the working conditions of the constant temperature and humidity chamber are stable, put the glass container containing the composite material in and adsorb the composite material. During this period, record the weight every 30 minutes until the weight no longer increases. Finally, the adsorption amount of the magnesium sulfate / diatomaceous earth composite thermochemical heat storage material is 0.342 g (water) / g (material).
[0036] Example 4
[0037] Weigh 10g of porous material diatomaceous earth powder, place it in a drying oven, dry it at 150°C for 12h, take it out and cool it to room temperature, then store it in a dry place, weigh 14g of anhydrous magnesium sulfate powder and 40g of deionized water to prepare a magnesium sulfate salt solution, weigh 10g of dried diatomaceous earth, slowly drop the prepared salt solution into the diatomaceous earth powder, gently stir when adding the solution to ensure uniform adsorption without destroying the porous structure of the diatomaceous earth, and ensure that the diatomaceous earth is apparently dry until the adsorption is complete, let it stand at room temperature for 4h to allow the salt solution to evenly penetrate into the pores of the diatomaceous earth, then place the wet composite material in a drying oven, evacuate it to 0.08MP to accelerate the separation of moisture, keep it at a constant temperature of 150°C for 10h to fully remove moisture, and obtain a magnesium sulfate / diatomaceous earth composite thermochemical heat storage material with a loading rate of 55%.
[0038] Weigh 5 g of the prepared composite thermochemical heat storage material and place it in a glass container. Set the constant temperature and humidity chamber temperature to 25°C and the relative humidity to 80% RH. After the working conditions of the constant temperature and humidity chamber are stable, put the glass container containing the composite material in and adsorb the composite material. During this period, record the weight every 30 minutes until the weight no longer increases. Finally, the adsorption amount of the magnesium sulfate / diatomaceous earth composite thermochemical heat storage material is 0.370 g (water) / g (material).
Claims
1. A method for preparing a magnesium sulfate / diatomite composite thermochemical heat storage material, characterized in that: The specific steps are as follows: (1) Weigh a certain mass of porous material diatomaceous earth and place it in a drying oven for a period of time to remove the moisture that may be adsorbed therein. After drying, seal and store it. (2) Deionized water and anhydrous magnesium sulfate powder are mixed, stirred for a while, and then placed in an ultrasonic cleaning machine for full stirring to obtain uniformly mixed magnesium sulfate solutions with different mass fractions. (3) slowly dripping the magnesium sulfate solution obtained in step (2) into the porous material diatomaceous earth obtained by drying in step (1), keeping the surface of the diatomaceous earth dry during the dripping process until the adsorption is complete, leaving it to stand at room temperature for a period of time, and then placing it in a drying oven for drying. After drying, it is stored in a dry environment to obtain a magnesium sulfate / diatomaceous earth composite thermochemical heat storage material.
2. The method for preparing the magnesium sulfate / diatomite composite thermochemical heat storage material according to claim 1, characterized in that: The porous material diatomaceous earth described in steps (1) and (3) is 200 mesh diatomaceous earth.
3. The method for preparing the magnesium sulfate / diatomite composite thermochemical heat storage material according to claim 1, characterized in that: The mass ratio of distilled water to porous material diatomaceous earth in step (1) is (1.8-2.2), and the mass ratio of deionized water to anhydrous magnesium sulfate powder in step (2) is (10-2):
1.
4. The method for preparing the magnesium sulfate / diatomite composite thermochemical heat storage material according to claim 1, characterized in that: The stirring time of the solution in step (2) is 3 h.
5. The method for preparing the magnesium sulfate / diatomite composite thermochemical heat storage material according to claim 1, characterized in that: The mass of the solution impregnated in step (3) is about twice the mass of the diatomaceous earth, and the solution is placed indoors for 10 to 12 hours, the drying temperature is 150° C., and the drying time is 12 hours.
Citation Information
Patent Citations
Preparation method of magnesium sulfate / zeolite molecular sieve composite heat storage material
CN107502310A
Preparation method of magnesium trisilicate andmagnesium sulfate mixed salt / zeolite molecular sieve composite heat storage material
CN107760279A
Composite heat storage material containing dihydrate salt
CN110079280A
Composite chemical adsorption material based on porous clay and preparation method of composite chemical adsorption material
CN110743490A
Thermochemical adsorption heat storage material capable of efficiently transferring mass and heat and preparation method thereof
CN114015418A